Electricity Market Management Through Optimum Installation of Distributed Generation Sources and Optimum Placement Based on LMP and ISC - Muhammad Hammad Saeed; Sajid Iqbal; Basheer Ahmed Kalwar (Advances in Engineering and Intelligence Systems)
In this paper, a novel method based on LMP with the title of system cost index is presented for the optimum placement of distributed generation (DG) sources in the electricity market based on optimum power flow. Along with optimum placement, the optimum size of these sources is also calculated. Desirable locations are determined for optimum DG order based on local margin price (LMP). The LMP index is defined in the Lagrange coefficient of active power flow in each bus. Another index used to find desirable locations for DG placement is the customer payment (CP) index, which can be calculated for each bus by multiplying LMP by busload. In the presented method, in addition to considering two fundamental problems, i.e., system cost and line congestion, in the electricity market, the determination of the optimum size of DG is a criterion that is introduced as the system cost index (SCI). The optimum buses are selected based on considering the SCI criterion; two methods of bus ranking based on LMP and CP are used. In the LMP ranking, the bus with the highest LMP and the bus with the highest consumed power are chosen in the CP method. The proposed method is implemented on the modified IEEE 9-bus system. The simulation results suggest that the proposed method satisfies the engineering aspect of operation and the economic aspect of the process in the market. The optimum placement of DGs in the market environment leads to a decrease in system cost and management of line congestion.